Pengaruh Nilai Hedonis dan Nilai Utilitarian terhadap Niat Pembelian Tas Lokal pada Generasi Z Wanita - Viola De Yusa (Reviu Akuntansi, Manajemen, dan Bisnis, 2023)
Purpose: The purpose of this study is to look into the impact of hedonic and utilitarian values on Generation Z women's propensity to buy local bags. Methodology/approach: This research method uses a quantitative approach by collecting data through surveys and questionnaires. The sample in this study amounted to 160 respondents. SmartPLS and measurement model techniques were used to conduct this research. Results/findings: The research results show that hedonic value and utilitarian value have a significant influence on the intention to purchase local bags among Generation Z women. Hedonic value contributes positively to purchase intention. Utilitarian value also contributes positively to purchase intention, indicating that the usefulness and benefits provided by local bags also influence generation Z women's purchase intention. Limitations: This study has limitations, such as limited sample size and limitations in generalizing the results to other populations. Future research can expand the scope and explore other aspects that can influence the intention to purchase local bags among Generation Z women, such as relevant social, psychological and cultural factors. Contribution: For those involved in the local fashion business and marketers creating tailored marketing tactics, these findings have significant ramifications. The attractiveness and desire of Generation Z women to purchase local goods can be increased by raising the hedonic value and functional value of local bag products. The findings of this study can help assist the creation of products that are better adapted to the demands of female generation Z consumers by revealing their preferences and driving forces while making local bag purchases.